ASSESSING THE BIOACTIVITY AND ANTIOXIDATIVE PROPERTIES OF SOME COMPOUNDS ISOLATED FROM ABUTILON HIRTUM (LAM.) - Mortady Hamed, Manal; Refahy, Laila Abdel-ghany; Abdel-aziz, Mohamed Sayed (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: The present study on the methanol extract of Abutilon hirtum (Lam.) [Malvaceae] afforded ten compounds. Findings from this assessment indicated that A. hirtum leaves possessed vast potential as medicinal product especially in liver cancer treatment. Methods: Dried-powdered leaves were boiled under reflux in 10 L of petroleum ether for 8 hrs. After filtration, the solvent was evaporated; afforded 15 g of petroleum ether extract followed by boiling with reflux for 8 hrs with chloroform, then filtration and the residue was evaporated to give 34 g chloroform extract. Ethyl acetate was added and refluxed for 8 hrs, then filtration and evaporation to give 31 g ethyl acetate extract. Finally the leaves were refluxed with 10 L of 85 % aqueous MeOH, after cooling, the solution was filtered and evaporated and the residue was 210 g methanol extract then the residue was dissolved in de-ionized water (250 ml), then the salt was removed by adding excess methanol solution (2.5 L), and finally filtered. The cytotoxicity of the isolated compounds was evaluated towards HepG2 liver-carcinoma cell line using MTT assay, the antimicrobial activity was tested using the Disc agar plate method and the total antioxidant capacity was determined according to phosphomolybdenum method. Results: The isolated compounds identified as methyl gallate, cuneataside E, bergapten, gallic acid, ellagic acid, epigallocatechin-3-O-gallate, kaempferol-3-O-Î±-L-rhamnoside, benzyl-1-O-Î²-D-glucopyranoside, 2(4-hydroxyphenyl)ethyl-O-Î²-D-glucopyranoside and Î²-sitosterol. All the isolated compounds are known; but they were isolated from Abutilon hirtum for the first time. Conclusion: This report may serve as a footprint concerning the biological and pharmacological activities of A. hirtum leaves. Keywords: Abutilon hirtum, Malvaceae, HepG2, Phenolics, Antioxidant. Â 